Hemolytic reactions in the hemolymph of bivalve Sinonovacula constricta show complement-like activity. Issue 79 (August 2018) - Niu, Donghong; Xiong, Ya; Peng, Maoxiao; Meng, Xue; Lan, Tianyi; Li, Jiale
Abstract: The complement-like hemolysis method was used to determine the total complement-like activity of the plasma of Sinonovacula constricta . In this study, the effects of both physical and chemical conditions on complement hemolysis of S. constricta were measured. Physical conditions included proportion ( S. constricta plasma: 2% rabbit red blood cells), temperature, time, and incubation, while the chemical factors consisted of Lipopolysaccharide (LPS), Flagellin (FLA), Zymosan, Peptidoglycan (PGN), Phenylmethanesulfonyl fluoride (PMSF), Methylamine, and Poly (I: C). The results showed that LPS, flagellin, Zymosan and PGN could activate complement-like activity of S. constricta plasma and cause hemolysis. PMSF and methylamine inhibited complement-like activity, resulting in the disappearance of hemolysis. Poly (I: C) had no effect on plasma complement-like activity. When the reaction temperature was less than 50 °C, hemolytic activity would increase following an increase in temperature. The ratio of plasma to rabbit blood cells had a great impact on the rate of hemolysis. Additionally, incubation with low speed oscillation could improve the hemolysis rate. It is indicated that the hemolytic reactions in the hemolymph of bivalve S. constricta show complement-like activity. The results contribute to further research on immune function of complement in bivalve. Highlights: The complement-like hemolysis method was used to determine the total complement activity of the serum of Sinonovacula constricta . The several biochemical factors play activating or inhibitory roles in hemolytic reactions. The ratio of serum to rabbit blood cells and incubation with low speed oscillation have a great impact on the rate of hemolysis.